Outstanding marketing students of the Philippines - De La Salle University, Manila (Animo Repository, 2001)
Special commendations were given to: Michelle Frances Cruz and Leslie Anne Patalinghug, winners, Ten Outstanding Marketing Students of the Philippines Jonah Genilza, Gold Medalist, 400 meter dash, Macao Athletic Competition Prashant Srinivasan, winner, Search for the Three Most Outstanding Foreign Students of the Philippines. during the Student Awards 2001.